Analysis of the IHP Decision on BWF Sanctions Against Eight Indonesian Badminton Players in Sports Law Violations - Fadhilatul Ma'rifah Fi Kamilatil Mahabbah; Renanda Ayu Krisdianty (Faculty of Law Universitas Negeri Surabaya, 2025)
This article analyzes the decision of the Independent Hearing Panel (IHP) of the Badminton World Federation (BWF) concerning eight Indonesian badminton players involved in a match fixing case. This research aims to examine the legal considerations used by the IHP in imposing sanctions and to assess how the principle of Lex Sportiva was applied in resolving international sports disputes. This research employs normative legal methods through statute approach, conceptual approach, and case approach. The findings indicate that the IHP exercised its authority based on Articles 29 and 31 of the BWF Statutes and applied the balance of probabilities standard. The defendants were found to have violated various provisions of the BWF Code of Conduct (2012, 2016, and 2017 editions), particularly in relation to match manipulation, betting activities, failure to report, and lack of cooperation during investigations. This decision illustrates the application of Lex Sportiva, a body of transnational norms developed in international sports law. By referring to BWF regulations and jurisprudence from the Court of Arbitration for Sport (CAS), the panel emphasized the importance of maintaining sports integrity through firm sanctions. The ruling serves not only to penalize but also to safeguard the values of fair play and public trust in the sport of badminton.